School Principal's Role in Improving Learning Quality - Usholicchah, Nurnida; Akhmad Saputra, Ade (IJLHE: International Journal of Language, Humanities, and Education, 2024)
The purpose of this study is to understand the important role of one of the tasks of the Principal (school principal), namely monitoring educators and students in order to improve and improve the learning process at SDN 6 Pemulutan Selatan by knowing the objectives, constraints and benefits of supervising the quality of learning. As it is known that supervision carried out by the principal is part of the management function. The research methodology applied is qualitative, where researchers are directly involved in collecting data at the research location. The object of the research is the principal's role in monitoring the learning process at school. Data were collected through direct observation and interviews with principals and teachers. The implications of this study provide a deeper understanding of the significant role of school principals as supervisors in improving the quality of learning. Related to this study, the researcher found that awareness of supervisory activities by school principals at SDN 6 Pemulutan Selatan is still lacking in attention and implementation. The results showed that supervision by principals of the learning process and teacher performance had a positive impact on improving the quality of learning. The results of this discussion can be seen that first, by supervising learning, principals can evaluate the teaching methods used, the effectiveness of learning, and student responses to learning. Second, the obstacles to supervising the quality of learning can be caused by factors such as incomplete infrastructure and limited time for school principals. Third, the benefits of monitoring the quality of learning are getting information on the teaching and learning process as evaluation material.